Ketimpangan Beban Tanggung Jawab Hukum Antara Dokter dan Perawat dalam Sistem Pelayanan Kesehatan - Emirza Nur Wicaksono (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
This research examines the disproportionate allocation of legal responsibility between doctors and nurses in Indonesia’s health care system and proposes measures to reorganize accountability in a more fair and proportional way. The issue addressed stems from shortcomings in existing regulations, which have not yet ensured legal certainty or balanced legal protection for both professions in clinical practice. The study uses a normative juridical method, applying both statutory and conceptual approaches. The statutory approach reviews laws and regulations that govern professional authority and legal liability of doctors and nurses, while the conceptual approach analyzes legal principles, doctrines, and concepts related to professional responsibility in health services. Legal materials are collected through library research, including primary, secondary, and tertiary legal sources, and are analyzed using qualitative descriptive methods. The results show that although statutory provisions formally regulate the distribution of authority and responsibility between doctors and nurses, there are still normative uncertainties, overlapping regulations, and legal gaps. These issues may lead to an unequal burden of legal responsibility, particularly in cases involving medical errors or negligence. Such conditions weaken legal protection for nurses and can negatively affect the quality of health care delivery. The study concludes that regulatory reform is needed to clarify legal responsibility in accordance with professional authority and to implement a more just and proportional system of accountability. The findings are expected to enrich health law studies and provide guidance for policymakers in developing a fairer legal responsibility framework for health professionals.